Development of the ESQ Method With Hypnoteaching to Improve the Discipline of Diktuk Polri Students - Junaidi, AKH; Ansori, Ansori (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This study aims to determine the effectiveness of applying Hypnoteaching-assisted ESQ in improving the literacy discipline of POLRI Diktuk Education students. The research method used is the Research and Development method. The instruments used in this study were observation, questionnaires, and interview guidelines. Testing the effectiveness in this study using qualitative and quantitative data. The sample used was 25 students at SPN Cisarua, West Bandung Regency. This study found that the average timeliness of attendance in learning activities was quite good. The development of the Hypnoteaching-assisted ESQ method was carried out in two stages: 1) development of a hypothetical draft and 2) conceptual and empirical testing by experts as a process of rational, structural and editorial assessment. Based on the results of the disciplinary questionnaire, there was an increase after participating in ESQ training with the help of hypnoteaching. The application of hypnoteaching in ESQ training also has some drawbacks. Students feel they do not get the same attention from educators and the number of meetings is still limited. The conclusion of this study is that there are significant differences in discipline between before and after receiving hypnoteaching-assisted ESQ training.